What kind of involvement for national minorities in the political decision-making process? - Vidau, Zaira (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
The paper examines participation through representation in elected bodies and participation in consultative bodies for Slovenes in Italy. The legal framework for political participation for Slovenes in Italy is also discussed. Recent legal reforms of the Italian public administration at national and regional levels are considered since they reduce the level of the participation of Slovene representatives in decision-making processes, as well as limiting the public use of Slovene. The analysis shows that the presence of Slovene-speaking elected representatives in some municipalities has not yet been accomplished. Moreover, the question of various forms of political participation at the level of legal provisions on the rights of Slovenes in Italy remains unsettled.
Keywords: Italija; Italy; narodne manjšine; zamejski Slovenci; politična participacija; zakonodaja; pravno varstvo